Integrative Analysis of the Impact of Final Disposal Sites (TPA) on the Quality of Slum Settlements and Community Participation in Spatial Planning in Urban Areas - Siti Aisyah Siahaan; Cut Nuraini; Abdi Sugiarto (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Slum settlements developing around Final Disposal Sites (TPA) represent a complex phenomenon that affects the quality of the urban living environment. In Karo Regency, the proximity of the TPA to residential areas has raised various issues such as air pollution, declining sanitation quality, and limited community participation in spatial planning processes. This study aims to analyze the influence of Distance to the TPA (X1), Length of Residence (X2), Community Participation (X3), Perception of TPA Impact (X4), and Household Income (X5) on the Quality of Slum Settlements (Y). A quantitative approach was applied using a multiple linear regression model, based on primary data from 200 respondents residing in areas affected by the TPA. The analysis revealed that, simultaneously, the four independent variables (X1–X4) significantly influence settlement quality, whereas household income does not show a significant effect. Partially, Distance to the TPA and Length of Residence have negative effects, while Perception of TPA Impact has a positive effect. Interestingly, Community Participation shows a negative influence, indicating ineffective engagement in environmental management. The R² value of 0.016 suggests that the model explains only a small portion of the variation, yet the F-test significance supports the overall model's relevance. Recommendations from this study include the importance of establishing a minimum 300-meter buffer zone between the TPA and residential areas, implementing sanitary landfill methods to replace open dumping systems, forming environmentally-based community forums with advocacy strength, and conducting community-based waste management training focusing on high-risk households. Strengthening participatory approaches through integration into village and sub-district spatial planning is essential for managing environmental impacts collaboratively and sustainably.